Hubungan Dukungan Organisasi, Beban Kerja dan Motivasi Kerja dengan Kinerja Pegawai Dinas Kesehatan Kota Samarinda Tahun 2025 - Fatimatuzzahra, Siti; Adrianto, Ratno; AR., Chaerunnisa; Sumarni, Sumarni; Masithah, Masithah (Universitas Wiralodra, 2025)
Human resources played an important role in the management of an organization in achieving its goals, as an organization required human resources to manage the systems within it. The role of human resources in an organization was very important in determining whether the organization was effective or not. The effectiveness of human resources could be demonstrated by the processes that took place within the organization. One of these was through employee performance. Therefore, the sustainability of the organization depended on employee performance. This employee performance could be influenced by organizational support, workload, and work motivation. This research aimed to determine the relationship between organizational support, workload, and work motivation with the performance of employees at the Dinas Kesehatan Kota Samarinda. The research design was cross-sectional with a population of employees from the Dinas Kesehatan Kota Samarinda. The sample for this study consisted of 50 employees from the Dinas Kesehatan Kota Samarinda (proportional stratified random sampling). The instrument used in this research was a questionnaire. The statistical test employed was the Fisher exact test. The results of the bivariate analysis in this study indicated that there was a relationship between work motivation and employee performance (p=0.016). However, no relationship was found between organizational support and employee performance (p=0.423). Similarly, no relationship was found between workload and employee performance (p=0.216). The conclusion of this study was that there was a relationship between work motivation and the performance of employees at Dinas Kesehatan Kota Samarinda, while there was no relationship between organizational support and workload with employee performance. Recommendations for the agency included continuously improving employee performance, especially in aspects of good motivation, and for future researchers to further investigate with other variables or in different locations.